Recent developments of quantum dot based micro-LED based on non-radiative energy transfer mechanism - Xiaotong Fan (Institue of Optics and Electronics, Chinese Academy of Sciences, 2021)
With regard to micro-light-emitting diodes (micro-LEDs), their excellent brightness, low energy consumption, and ultra-high resolution are significant advantages. However, the large size of traditional inorganic phosphors and the number of side defects have restricted the practical applications of small sized micro-LEDs. Recently, quantum dot (QD) and non-radiative energy transfer (NRET) have been proposed to solve existing problems. QDs possess nanoscale dimensions and high luminous efficiency, and they are suitable for NRET because they are able to nearly contact the micro-LED chip. The NRET between QDs and micro-LED chip further improves the color conversion efficiency (CCE) and effective quantum yield (EQY) of full-color micro-LED devices. In this review, we discuss the NRET mechanism for QD micro-LED devices, and then nano-pillar LED, nano-hole LED, and nano-ring LED are introduced in detail. These structures are beneficial to the NRET between QD and micro-LED, especially nano-ring LED. Finally, the challenges and future envisions have also been described.